PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA KUD CATUR GUNA AMERTHA - Putri Anggreni (STIMI Handayani Denpasar, 2017)
This study aims to find out what there is significant influence betweenleadership style and work discipline on employee motivation KUD Catur GunaAmertha, Yehembang Village, District Mendoyo, Jembrana. The research concludesthat: Firstly, there is significant influence leadership style and work disciplineon employee motivation KUD Catur Guna Amertha, Yehembang Village, DistrictMendoyo, Jembrana, partially evident from the results count each partial correlationfor both variables showed that rx1y = 0.792 with figures significance of 0.000 andrx2y = 0.610 with 0.007 significance figures. Where both figures obtained significancesmaller than 0.05. Partial means indicates that these two variables have a relationshipthat is very significant to employee motivation. Secondly, there is a significant effectof leadership style and work discipline on employee motivation KUD Catur GunaAmertha Yehembang Village, District Mendoyo, Jembrana, simultaneously this canbe proven by obtaining F hitung = 35.306 with a significance figure of 0.000. Wherethe significance of the figures obtained are smaller than 0.005, means simultaneouslyreject H0 and accept H1. Thirdly there is a significant relationship leadership styleand work discipline on employee motivation KUD Catur Guna Amertha YehembangVillage, District Mendoyo, Jembrana, that of the correlation coefficient is jointlyacquired by rx1x2y = 0.919 with 0.000 significance figure where this number issmaller than in figure 0.05.